2014
DOI: 10.30782/uluvfd.163481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Sample Types for Salmonella Detection From Chicken Layer Breeder Flocks

Abstract: The object of this study was to detect Salmonella from different chicken samples in same flocks to compare sample types for Salmonella detection by both International Organization for Standardization Method 6579:2002/Amd 1:2007 (ISO) and as molecular by a polymerase chain reaction (PCR) method. Salmonellosis is a zoonotic infection and apart from this, infection can be transmitted via vertically to embryo, and this is very important for breeding flocks. A total of 115 samples, comprised of 451 individual sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…They stated that the probability of isolation due to other contaminant bacterial strains is lower when cultivated from stool, and the chances of catching positive animals by PCR are higher. Similarly, Çarlı et al (2001) and Kahya et al (2013) found the advantages of PCR in detecting agent in poultry. Olivera et al (2003) compared the standard isolation and post-culture PCR methods and found that the second method is more sensitive and shortens the time required for diagnosis.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…They stated that the probability of isolation due to other contaminant bacterial strains is lower when cultivated from stool, and the chances of catching positive animals by PCR are higher. Similarly, Çarlı et al (2001) and Kahya et al (2013) found the advantages of PCR in detecting agent in poultry. Olivera et al (2003) compared the standard isolation and post-culture PCR methods and found that the second method is more sensitive and shortens the time required for diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…It was incubated at 37°C for 24 hours. (Kahya et al, 2013;WHO 2010, Van Immersel et al, 2004. At the end of incubation period, black colonies and black-centered (H2S-positive) colonies with periphere changing from pink to red in XLD Agar; white and red colonies surrounded by red zones in BG Agar, colorless semi-transparent yellowish colonies in MacConkey Agar were evaluated as suspicious.…”
Section: Bacteriological Examinationmentioning
confidence: 99%
See 3 more Smart Citations